2019
DOI: 10.1108/ijcst-12-2018-0163
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion behaviors of liquid ammonia in the cellulose based on molecular dynamics simulation

Abstract: Purpose In the textile industry, liquid ammonia treatment is an important way to modify the structure of natural fibers. The purpose of this paper is to reveal the diffusion behaviors of liquid ammonia in cellulose. Design/methodology/approach To analysis the diffusion behaviors of liquid ammonia in cellulose, the cellulose model and the system of ammonia and cellulose are built. Infrared spectrum is carried out to test the model of cellulose, which is found to agree with experiment. Diffusion coefficients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…When the energy in the system is constant or uctuates around the constant value, the uctuation amplitude of the system temperature is within 25°C, indicating that the system tends to reach equilibrium [27]. The subsequent dynamic simulation is performed on this basis, and the results are more reliable.…”
Section: System Energymentioning
confidence: 99%
“…When the energy in the system is constant or uctuates around the constant value, the uctuation amplitude of the system temperature is within 25°C, indicating that the system tends to reach equilibrium [27]. The subsequent dynamic simulation is performed on this basis, and the results are more reliable.…”
Section: System Energymentioning
confidence: 99%
“…2022 Liquid ammonia has super permeability and fluidity, and easily penetrates into the fiber to change the fiber crystallinity. 23 In this article, liquid ammonia was introduced to partially peel off the surface scales of wool, 2426 so as to promote the modification of wool by protease and reduce the hydrolysis of CMC layer. However, the water-soluble polyurethane with good permeability and elasticity 19,27,28 was used in the shrink-resistant finishing of wool.…”
Section: Introductionmentioning
confidence: 99%
“…Khazraji and Robert (2013) found that the cellulose polymer has strong reactivity with water molecules, and water molecules easily form a hydrogen bonds with the cellulose chain. Huang et al (2019) revealed that ammonia molecules increase the end distance of cellulose Iβ and thus enhance its compliance. Wang et al (2020b) found that the mass fraction of water molecules has a greater impact on bamboo heat treatment through molecular dynamics simulation, and cellulose has the best mechanical properties when the mass fraction of water was 3% for heat treatment simulation.…”
Section: Introductionmentioning
confidence: 99%